Trans-Fascial Placement of a High, Sub Muscular Reservoir in Patients Following Radical Cystectomy: Safety, Efficacy, and Predictability of Final Reservoir Location Verified With Abdominal Imaging. Issue 2 (1st February 2019) - Kava, Bruce R.; Lopategui, Diana M.; Levine, Amanda; Ramasamy, Ranjith
Abstract: Introduction: With the increasing utilization of ectopic reservoir placement during multicomponent penile implant surgery, safety concerns have been raised about whether passing the reservoir through the floor of the inguinal canal consistently results in placement of the reservoir within the correct location. Aim: To evaluate the safety, efficacy, and patient satisfaction associated with direct-vision, trans-fascial sub muscular reservoir placement in consecutive patients who had previously undergone radical cystectomy. Methods: Perioperative data, complications, and follow up for the 12 cystectomy patients were evaluated using a comprehensive database of consecutive patients undergoing penile prosthesis placement at our center. Efficacy and patient satisfaction were based upon responses to the Erectile Function and Satisfaction Domains of the International Index of Erectile Function (IIEF). Taking advantage of the need for post cystectomy imaging in monitoring for cancer recurrence, we reviewed post- implant imaging with the purpose of ascertaining the final reservoir location. Main Outcome Measure: Using intraoperative photographs, we describe the technique of trans-fascial sub muscular reservoir placement. Perioperative complications, device efficacy and satisfaction, and the accuracy of reservoir placement are also evaluated. Results: Average patient age was 65 ± 7 years old and the mean time between cystectomy and implant placement was 41 ± 29 months. With a mean follow up of 26 ± 21 months, complications included: 1 reservoir herniation and 1 high riding pump requiring repositioning. Mean IIEF-EF domain was 29.8 ± 0.5 and mean IIEF-satisfaction domain was 17.7 ± 4.5. Other than the herniated reservoir, imaging confirmed accurate reservoir placement in 8 of 9 cases. In 3 patients a small cephalad portion of the reservoir extends posteriorly into the peritoneal or preperitoneal space, with no clinical consequences. Clinical Implications: Ectopic reservoir placement using a trans-fascial submuscular approach seems to be a safe method for multicomponent penile implant surgery in patients who have undergone radical cystectomy. Post-implant imaging confirms that the device is consistently placed in the correct sub muscular location. Strengths & Limitations: This is a novel approach to performing the procedure and a practical manner to ascertain the reservoir position. The limited number of patients prevents generalization of our findings. Conclusion: Trans-fascial, sub muscular reservoir placement is a safe means of ectopically placing the reservoir of a multicomponent penile implant following radical cystectomy. Post implant IIEF scores indicate high device efficacy and patient satisfaction. Post implant imaging confirms that the reservoir is almost always in the desired location.